Pro ASP.NET SharePoint 2010 Solutions: Techniques for Building SharePoint Functionality into ASP.NET Applications - Milner, Dave (Apress, 2012)
Code re-use is the Holy Grail of software development. Countless hours of refactoring, countless books, countless software development tools, components, IDEs, and platforms have been dedicated to pursue this elusive quality. Why is this? As software consumers, we are used to seeing very rapid advancements in technology. Every year, we see more amazing things accomplished in hardware and software. We see new gadgets, new technologies, and new concepts all conspiring in new and wonderful ways to make our world smaller and more manageable. The pace is almost beyond comprehension. When you think about where we have come from and some of the history of computing, it’s mind-boggling. We now carry in our pocket in a mobile device the computing power that used to take up an entire building. We can reach around the world at the speed of light to connect to information and people. We can store more information than our mind can comprehend on a device the size of our thumb. And we have built for ourselves somewhat of an expectation of magic and miracles.